The effect of lasalocid sodium on growth performance and possible coccidiosis in weaned akkaraman lambs - Şakir Doğan TUNCER; Behiç COŞKUN; Rıfat CANTORAY; Mehmet Ali TEKEŞ (Eurasian Journal of Veterinary Sciences)
This experiment was carried out to investigate the effects of Na -lasalocid that was added into concentrate mixtures in 25, 50 and 75 g per ton on growth performance and against the possible coccidia infection of lambs. In the experiment, 40 Akkaraman male lambs with 3.5 - 4 months old were used. The research works were conducted as 4 groups for the period of 84 days. The ratian of the control group did not contain any Na-lasalocid. The average of final weights of lambs in the groups were 47.41; 48.91; 49.98 and 49.96 kg respectively, (P>0.05). Average daily weight gain was found to be 260 g in the control group; 262, 281 and 280 g in the other groups, respectively, (P > 0.05). The concentrates and wheat straw fed to the lambs ad libitum. Total feed consumption for all groups w ere 1646, 1648, 1650 and 1709 g respectively. The concentrate intake per kg weight gain were found to be 5.896, 5.744, 5.402 and 5.571 kg, respectively. According to these results, it would asserted that the groups feed with lasalocid improved the feed canversion rate more than the control group at the level of 2.58%, 8.38%, and 5.51 %, respectively. The numbers of coccidia oocysts were found to be 6ı33, 5ıoo, 6000 and 7833 in ı g of feces sample at the beginning of the experiment. However, the counts of oocysts were sharply reduced after the treatment with Na-lasalocid at all levels. These values were found to be 4033, 38, 30 and 0, respectively, at the end of the experiment. Although 25 g g/ton Na-lasalocid did not improve the growth performance, the same level was highly effective in reducing the cocysts counts. On the other hand, spesifically 50 g/ton Na- lasalocid had both possitive effect on growth performance and reducing oocysts numbers. As a result, the use of this level would be strongly recommended in intensive lamb feeding.